A Contribution in a Practical Study to Treat Galleria MellonellaL. (Lepidoptera; Pyralidae) Which Affects Honey Bee Colonies by Temperature Treatment in Stores - Habeb, Faisal; Moukayees, Khalil (Latakia University Journal -Biological Sciences Series, 2013)
This research studied the effect of temperature on GalleriamellonellaL. of the second, third, andpupal stages, after culturingthemin vitro in an artificial environment from the egg stage till the pupal stage. This study which was carried out in 2011 shows that the number of larval stages was6and the durationof Larvaldevelopment tillthe pupal stage was 21days. This is doneusing a computer program SPSS,(Anova test)to define the least significant difference at level 5%. The statistical results showed that the effect of high temperature was better than the effect of low temperature in reducingthe development and number ofGalleria mellonella on the combwax so that the death rate at 48C0for 6 hours was 100% in Larva and 95% in the pupal stage taking into consideration the identical distribution of hot air among wax. So in case coolplaces less than (5c0) were found, beeKeepers can benefit fromthe low temperature practices to protectcomb wax from infection with Galleria mellonella